Analysis GISWAF on the Interest of Waqf Students: A Case Study on UNIDA Gontor - Afif, Mufti; Muzaki, Rofi; Sa’id, Roudhoh Hannaaris; Maulana, Hartomi (Indonesian Journal of Islamic Economics and Finance, 2024)
The literacy of Indonesian society regarding waqf is still relatively low. People often confuse waqf with charity (sodaqoh) and voluntary contributions (infak). Similarly, the literacy among university students about waqf is also lacking. The GISWAF "Gerakan Indonesia sadar wakaf" movement has introduced a seminar activity called "Waqf Literacy Seminar" for students at Universitas Darussalam Gontor. This research employs a qualitative descriptive method, involving interviews with 14 Students considered sufficient to reach the data saturation point, as well as observation and documentation, to explore the understanding and awareness of waqf among students. This research is to gauge the interest of students in waqf by examining their understanding, awareness, and future intentions regarding waqf. The specific this research is to evaluate how effective GISWAF is in increasing UNIDA Gontor students' desire to give waqf. The findings from the study indicate interest, 5 students (36%) are interested in practicing waqf literacy to the community, 4 students (29%) are interested in studying more deeply about waqf, 4 students (29%) are interested in doing waqf, and 1 student (7%) is interested in still wanting to learn about waqf, and 0 students do not want to learn waqf (0%).